Low basal friction‐controlled geometry and kinematics of accretionary wedges from analogue experiments. (29th August 2019) - Deng, Bin; Fan, Caiwei; He, Yu; Lai, Dong; Jiang, Ziran; Wang, Xinjian; Liu, Shugen; Jansa, Luba
Abstract : Cohesion and friction coefficients are fundamental parameters of granular materials used in analogue experiments. Our six models, comprising two sets of quartz sand with a 0–3 mm thickness of basal glass beads, illustrate that accretionary wedges with high basal friction have relatively larger slope angles and heights, shorter wedge lengths, and larger numbers of faults with smaller spacings and displacements than wedges with low basal friction. It should be noted that the differences in the geometry and evolution of the two sets of homogeneous quartz sands are not distinct; however, the differences are substantial when the models have low basal friction of the glass beads. In particular, there are two different tendencies of growth in wedge height with progressive shortening, that is, progressive growth of wedge height with high basal friction and steady‐state growth of wedge height with basal glass beads. We thus infer that the wedge geometries in our experiments are preferentially controlled by the low basal friction achieved with glass beads. In particular, the basal décollement (even when thin) has a significant influence on the location and development of accretionary wedges, in contrast to the physical properties of brittle materials (e.g., friction coefficient and cohesion).